2020
DOI: 10.1111/1346-8138.15301
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features of rosacea in Changsha, China: A population‐based, cross‐sectional study

Abstract: Rosacea is a common chronic skin disorder of unknown etiology. While population prevalence rates range 0.2-22% in Europe and North America, prevalence in China is currently undetermined. We conducted a large populationbased case-control study to determine the present epidemiological status of rosacea in China, involving 10 095 participants aged 0-100 years (mean age, 35.5 ± 19.1; 50.5% female). A census of rosacea among 15 communities in Changsha in south central China was conducted with skin examination by bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 18 publications
4
47
0
Order By: Relevance
“…Therefore, in contrary to the findings of James et al our results suggest that rosacea is not associated with hypothyroidism. In another study conducted in China, researchers concluded that hyperthyroidism was associated with rosacea in females ( P < .05), while it was not associated with rosacea in males 8 . As per our findings, TSH, anti‐TPO, and anti‐TG values did not pose a risk for rosacea.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Therefore, in contrary to the findings of James et al our results suggest that rosacea is not associated with hypothyroidism. In another study conducted in China, researchers concluded that hyperthyroidism was associated with rosacea in females ( P < .05), while it was not associated with rosacea in males 8 . As per our findings, TSH, anti‐TPO, and anti‐TG values did not pose a risk for rosacea.…”
Section: Discussionsupporting
confidence: 80%
“…It primarily affects central facial convexities (cheeks, nose, chin, and forehead). It was reported that the incidence of rosacea was 5.46%, and it ranged between 0.09% in the Faroe Islands of Denmark and 22% in Caucasians 8 . Its prevalence was relatively low in countries populated by people with Fitzpatrick skin phototypes IV to V.…”
Section: Discussionmentioning
confidence: 99%
“…Rosacea is a common chronic inflammatory disease, which mainly affects the convex facial areas such as nose, cheek, chin, and glabella, with estimated prevalence ranging from 2% to 22% worldwide [1,2] and leading to impaired physical appearance, self-abasement, frustration, and poor quality of life in millions of patients with rosacea [3]. The clinical manifestations of rosacea are quite diversified, including flushing, erythema, angiotelectasis, papules, pustules, and phymatous changes [4], which vary largely from patient to patient, and some of these manifestations usually overlap [5].…”
Section: Introductionmentioning
confidence: 99%
“…Rosacea is a chronic inflammatory cutaneous disease with an estimated worldwide prevalence of 5.5% ( 1 ). In China, the prevalence of rosacea is up to 3.48% ( 2 ). Rosacea mostly affects facial areas and is characterized by recurrent flushing, telangiectasia, persistent erythema, phymas, papules, pustules, edema, and irritated eyes ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%